Effect of pH and molar ratio of pollutant to oxidant on a photochemical advanced oxidation process using hypochlorite - Kishimoto, Naoyuki (Environmental technology, 2015)
Ultra violet (UV)-photolysis of hydrogen peroxide (H2O2) is a conventional advanced oxidation process (AOP) and is advantageous in its simplicity, although H2O2 is costly. Accordingly, we tried to substitute H2O2 by hypochlorite in the photochemical AOP, and discussed the effect of pH and the molar ratio of a pollutant to hypochlorite on the process using 1,4-dioxane as a model pollutant. The photochemical treatment of hypochlorite solutions at a wavelength of 254 nm under various pH values revealed that the UV-photolysis of hypochlorous acid (HOCl) species mainly contributed to hydroxyl radical (•OH) production. The reaction efficiency, as defined by the molar ratio of removed 1,4-dioxane to consumed hypochlorite, deteriorated under higher pH levels due to the stronger radical scavenging effect of hypochlorite ion (ClO(-)) as compared to that of HOCl. The optimal pH for the UV-photolysis of hypochlorite as an AOP was found to be in the range of 3-6. The reaction efficiency at a high molar ratio of initial 1,4-dioxane to initial hypochlorite exceeded 100%, which was caused by the regeneration of HOCl from photochemically generated chlorine radicals (•Cl). Finally, the overall reaction of the UV-photolysis of HOCl was proposed on the basis of the radical reactions that were related to chlorine species, which suggested that the UV-photolysis of 1 mmol of HOCl stoichiometrically produced 2 mmol of •OH. Since the use of liquid chlorine is more economical than that of H2O2, the substitution of HOCl for H2O2 in the photochemical AOP was concluded to be feasible from the viewpoints of both stoichiometry and chemical costs